The Efficacy of the combined couple therapy approach based on acceptance and commitment with schema formulation (ACT/SF) on psychological flexibility and marital satisfaction - zahra borjali; javad molazade; nurallah mohammadi; abdolaziz aflakseir (مجله علوم روانشناختی, 2023)
Background: Integrating the approach based on acceptance and commitment with the approach of schema therapy to be more effective and respond to a wider range of couple problems has attracted the attention of researchers. Aims: This study aimed to determine the effectiveness of the combined approach of couple therapy based on acceptance and commitment with schema formulation (ACT/SF) on psychological flexibility and marital satisfaction. Methods: The research method used was quasi-experimental with a pre-test, post-test design, and a control group. The statistical population consisted of all couples referred to counseling centers in Qom in 2022. From this population, 16 couples (32 people) were selected using available sampling and divided into two groups: control and experimental. Both groups completed the ENRICH Marital Satisfaction Scale and the Acceptance and Action Questionnaire-II (AAQ-II) in the pre-test and post-test. The experimental group received therapeutic intervention for twelve 120-minute sessions. Data analysis was performed using covariance analysis at a significant level (P<0.05). Results: The results indicated that, by controlling the pre-test as a covariate variable, the experimental group experienced a significant increase in marital satisfaction with a strong effect size (η2= 0.62) and in psychological flexibility with a medium effect size (η2= 0.32). Conclusion: The combined approach of couple therapy based on acceptance and commitment with schema formulation significantly improves psychological flexibility and marital satisfaction. This is achieved through formulating problems, recognizing schemas, and becoming aware of cognitive distortions, which helps people understand and be more aware of their own and their spouse's psychological processes. Techniques based on acceptance and commitment are then used to encourage couples to improve their relationships based on their values.